Food Consumption in Adolescent Girls: How Far are We from Recommendations? (2024)
ABSTRACT: Introduction: Adequate energy and nutrient intake in adolescent girls are crucial for their health and that of their offspring. However, few studies evaluate food intake in this group. Objective: To assess the consumption pattern and prevalence of risk of deficiency in the usual intake of energy and nutrients in a group of adolescent girls from Medellin. Methods: This is a descriptive, cross-sectional study involving 1010 adolescents aged 14 to 20 years from the Popular, Manrique, and Villa Hermosa neighborhoods of Medellin. Food consumption was evaluated using a 24-hour recall (24HR), applied to all participants. A second 24HR was conducted on a random subsample (21%) to adjust for inter and intra-individual variability. Usual intake was estimated using EVINDI and PC-SIDE software and compared with the Estimated Average Requirement (EAR). To analyze consumption patterns, foods from the first recall were classified into six groups according to the Colombian Food-Based Dietary Guidelines (known in Spanish as GABA), and the Consumption Ratio Index, which is the ratio between consumed and recommended calories, was calculated. Descriptive statistics were used, and the prevalence of risk of deficiency in usual energy and nutrient intake was established using the Wilcoxon signedrank test and the effect size with the Biserial correlation coefficient, using Stata 16 and Jasp 0.14.1.0. Results: Most adolescents had a consumption of fruits, vegetables, dairy products, and proteins below the GABA recommendations, while intake of starches, fats, and sugars was equal to or above. There was evidence of an energy deficit and excessive intake of saturated fats and simple carbohydrates. Nearly all adolescents were at risk of deficiency in usual calcium and fiber intake; more than half in folate and iron, and one-third in proteins, thiamine, vitamin C, and zinc. Conclusions: The food consumption pattern of adolescent girls in Medellin is inadequate and poses risks of significant nutritional deficiencies that can have deleterious short- and long-term effects. Conflicts of Interest: none